Lactate uptake in the rumen and its contributions to subacute rumen acidosis of goats induced by high-grain diets - He, Banglin; Fan, Yaotian; Wang, Hongrong (Frontiers in Veterinary Science, 2022)
Rumen acidosis is the consequence of feeding rapidly fermentable grain diets and it is considered the most common nutritional disorder in intensive feeding ruminants. Due to that mechanism of catabolism and transformation is driven by multi-factors, the role of ruminal lactate and its contribution to subacute rumen acidosis has not been well defined yet. The aim of this study is to evaluate the effects of SARA on production, absorption, circulation and transformation of lactate in the rumen. In current study, twelve adult Saanen goats (44.5 ± 4.6 kg BW) equipped with permanent rumen cannul were taken ruminal samples and measured rumen fermentation parameters, organic acids production, microbial profiles and blood indicators to identify the occurrence of SARA. For further investigate the change of disappearance rate of ruminal lactate, the rumen fluid was collected and batch culture was performed. The results showed that the clearance rate of ruminal lactate was accelerated by SARA, and the concentration of ruminal lactate pool was stable. In addition, the rumen liquid dilution rate and the rumen liquid flow rate under SARA condition of goats were lower than that of normal condition, the ruminal lactate flow rate has no difference throughout the process of fermentation. However, in vitro data showed that the disappearance of lactate was reduced in SARA. By measuring the conversion of sodium L-[3-13C]-lactate in batch culture, it was found that the percentage of lactate converted to propionate was significantly lower in SARA treatment and 16.13% more lactate converted to butyrate under SARA condition. However, the percentage of lactate transformed into acetate and butyrate was significantly increased in SARA treatment than that of control. The relative population of total protozoa count in SARA was significantly reduced, while the relative population of Lactobacillus fermentum, Streptococcus bovis, Butyrivibrio fibrisolvens, Megasphaera elsdenii, and Selenomonas ruminantium in SARA treatment was significantly induced (P<0.05). It is concluded that the transformation of lactate into butyrate may promote the development of SARA, these findings provide to some references to the diet formulation for preventing SARA.